A comparison between some characteristics between positive and negative cloud to ground flashes observed in Sri Lanka and their seasonal variations - Sonnadara, D.U.J.; Fernando, I.M.K.; Weerasekera, A.B.; Liyanage, J.P. (My University, 2000)
Using a system of two Direction Finding (DF) stations, a total of 4120 cloud to ground (CG) flashes were recorded for 34 days during the months of February, May, June, August, September and October in 1999. It was observed that about 3% of the observed flashes were positive cloud to ground flashes and over 93% of the positive flashes were single stroke flashes. The percentage of positive flashes varied from 17% in June to less than 1% in September. The negative cloud to ground flashes had an average multiplicity of 2.1 and about 49% of them were single stroke flashes. The highest multiplicity of negative flashes was 2.7 in February and in all the other months this was below the average of 2.1. The highest percentage of single stroke negative flashes was 75% in June and the lowest was 34% in February
Keywords: Lightning measurements; Cloud to ground lightning